Soul enchilada - Gill, David Macinnis, 1963- (New York : Greenwillow Books, 2009)
When, after a demon appears to repossess her car, she discovers that both the car and her soul were given as collateral in a deal made with the Devil by her irascible grandfather, eighteen-year-old Bug Smoot, given two-days' grace, tries to find ways to outsmart the Devil and his minions.
edited hb 2015-06-16
Keywords: Conduct of life -- Juvenile fiction; Devil -- Juvenile fiction; Grandfathers -- Juvenile fiction; Racially mixed people -- Juvenile fiction; Conduct of life -- Fiction; Devil -- Fiction; Grandfathers -- Fiction; Racially mixed people -- Fiction